Simulacros de diversidade racial: permanência da ideologia do branqueamento no Brasil - Fernandes, Sérgio Rocha (2023)
The object of this research is a set of manifestations bringing together pictorial art, digital advertising and posts on social networks that put into discourse the ideology of whitening and situations experienced by Afro-Brazilian people who have suffered racial aggression because of their skin color, hair type, and physiognomic features. As a research problem, we investigated how such interactions install or not a dynamic for deconstructing the culture of racism, and what motivations sustain and promote this debate. The corpus is formed by the selection of two cultural productions in which the statements of the manifestations on ethnic-racial diversity will be analyzed, by means of a discourse survey, with the aim of examining and categorizing the different representations of values in circulation. The intention is to map these values in order to understand how the enunciative, figurative, and narrative strategies employed promote plurality and what impact they have on the understanding and debate about ethnic-racial diversity in its socio-economic-cultural context. We have selected the painting Ham's Redemption (1895) by the plastic artist Modesto Brocos y Gómez, which gives visibility to the ideology of whitening; and the Prouni campaign (2019), featured in several media outlets, pointed out as containing a racist positioning. The corpus of diversity manifestations will be analyzed according to the propositions of J.-M. Floch and A. C. de Oliveira on expressivity, which bring together the contributions of plastic analytical frameworks that articulate the formants of plasticity in figures and categories of expression with the participation of two other formants: the aesthesic and the rhythmic. The semiotics of A. J. Greimas, with the theoretical and methodological additions of E. Landowski for the analysis of the narrative level – in addition to his postulations for the study of identity and alterities in the social –, constitute the theoretical and methodological basis of this work